Arabidopsis bZIP18 and bZIP52 Accumulate in Nuclei Following Heat Stress where They Regulate the Expression of a Similar Set of Genes - Wiese, Anna J; Steinbachová, Lenka; Timofejeva, Ljudmilla; Čermák, Vojtěch; Klodová, Božena; Ganji, Ranjani S; Limones-Mendez, Mariana; Bokvaj, Pavel; Hafidh, Said; Potěšil, David; Honys, David (International journal of molecular sciences, 2021)
Heat stress (HS) is a major abiotic stress that negatively impacts crop yields across the globe. Plants respond to elevated temperatures by changing gene expression, mediated by transcription factors (TFs) functioning to enhance HS tolerance. The involvement of Group I bZIP TFs in the heat stress response (HSR) is not known. In this study, bZIP18 and bZIP52 were investigated for their possible role in the HSR. Localization experiments revealed their nuclear accumulation following heat stress, which was found to be triggered by dephosphorylation. Both TFs were found to possess two motifs containing serine residues that are candidates for phosphorylation. These motifs are recognized by 14-3-3 proteins, and bZIP18 and bZIP52 were found to bind 14-3-3 ε, the interaction of which sequesters them to the cytoplasm. Mutation of both residues abolished 14-3-3 ε interaction and led to a strict nuclear localization for both TFs. RNA-seq analysis revealed coordinated downregulation of several metabolic pathways including energy metabolism and translation, and upregulation of numerous lncRNAs in particular. These results support the idea that bZIP18 and bZIP52 are sequestered to the cytoplasm under control conditions, and that heat stress leads to their re-localization to nuclei, where they jointly regulate gene expression.
Keywords: proteiny huseníčku; reakce na tepelný šok; Cell Nucleus; heat stress; Arabidopsis; bZIP; RNA dlouhá nekódující; 14–3–3; Arabidopsis Proteins; buněčné jádro; RNA, Long Noncoding; regulace genové exprese u rostlin; Transcription Factors; proteiny 14-3-3; Gene Expression Regulation, Plant; transkripční faktory; Heat-Shock Response; transcriptomics; localization; 14-3-3 Proteins